Riesgo ergonómico por carga física en los trabajadores de las ladrilleras sector las Camelias - Iquitos. Loreto – Perú. 2023 - Romero Ocampo, Bryan Valentino (2025)
This study addresses ergonomic risks due to physical load among workers in the brick kilns of Las Camelias sector, Iquitos, who are exposed to heavy lifting, inadequate postures, and prolonged work hours. The objective was to identify and evaluate these risks, proposing corrective measures to improve occupational health. Based on occupational ergonomics principles and using the OWAS method, a descriptive and cross-sectional study was conducted in 2023, applying surveys and direct observation. The results showed that 78.3% of the workers handle loads exceeding 10 kg, and 58.3% work more than 8 hours daily, with common musculoskeletal complaints in the lower back (up to 55%) and hands and wrists (36%). The OWAS method revealed that between 50% and 75% of the adopted postures have harmful or severely harmful effects, particularly in drying, grinding, and kiln operation areas. It is concluded that there is a high ergonomic risk in these brick kilns, evidenced by the high prevalence of musculoskeletal disorders that affect productivity and workers' quality of life. Continuous exposure to demanding working conditions not only compromises physical health but can also lead to absenteeism and a significant reduction in overall worker well-being.